2021
DOI: 10.2147/amep.s335205
|View full text |Cite
|
Sign up to set email alerts
|

Internal Medicine Residents’ Perceptions of the Learning Environment of a Residency Training Program in Ethiopia: a Mixed Methods Study

Abstract: Introduction:The learning environment is an important determinant of the quality of medical education. Having a good learning climate leads to improved learning process, satisfaction with education, and helps achieve the goals of the curriculum. Assessment of the quality of learning environment helps with the identification of areas that need improvement. The aim of this study was to assess the learning environment of internal medicine training program in Ethiopia. Methods: A mixed methods study using a cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…The overall score is higher, similar to other studies in the developing world probably due to experienced teaching staff, and variation in resident workload (10,11,12,13). In contrast, studies from African continent report a very low score of 80 or lower due to an apparent lack of healthcare facilities, policies, curriculum for residents, and implementation in practice (14,15). Unusually, studies from the region (16, 17,18,19) showed a very low overall score of below 80, indicating plenty of problems in the residency program.…”
Section: Discussionsupporting
confidence: 77%
“…The overall score is higher, similar to other studies in the developing world probably due to experienced teaching staff, and variation in resident workload (10,11,12,13). In contrast, studies from African continent report a very low score of 80 or lower due to an apparent lack of healthcare facilities, policies, curriculum for residents, and implementation in practice (14,15). Unusually, studies from the region (16, 17,18,19) showed a very low overall score of below 80, indicating plenty of problems in the residency program.…”
Section: Discussionsupporting
confidence: 77%
“…Training atmosphere has evident effect on the overall satisfaction of trainees and the other sub construct of training process consequently it directly impact the quality of healthcare delivered. Our result showed that most of the psychiatry trainees were satisfied with practice of professionalism in relation with supervisors, colleagues, and worker [34]. A similar result were found in 2015 in a report about family medicine in Sudan which revealed that most of the residents were satisfied with practicing professionalism, 81.5% were satisfied about professional relationship with patients, 84.5% in relationship with collage and 78.5% in relationship with PHC teacher.…”
Section: Construct Of Trainees Satisfactionsupporting
confidence: 84%
“…The results of our study are consistent with those obtained in a study of internal medicine residents' perceptions of the training environment of the residency program in Ethiopia. There, four recurring themes were identified that negatively affect the learning environment, including excessive workload, inadequate teaching, unfavorable physical environment in the hospital, and lack of diagnostic and therapeutic methods [26]. During the focus groups, residents expressed their wishes for the use of best practices.…”
Section: Discussionmentioning
confidence: 99%